Cztery minuty. Hannah Arendt lekcja o zaimku - Roszak, Joanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The article attempts to analyse Hannah Arendt’s short essay “We Refugees” published in 1943 in a Jewish magazine The Menorah Journal in the context of the current humanitarian crisis (a crisis of reception policies) and peace studies. It also reconstructs refugee themes in the life trajectory of the author of Eichmann in Jerusalem. The author is confident that the essay “We Refugees” from seventy-seven years ago allows one to speak up repeating the questions concerning one of the key problems of contemporary world – the condition of the outcasts.